2021
DOI: 10.47738/ijiis.v4i2.108
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of E-Learning as One of the Information Technology-Based Learning Media on Student Learning Motivation

Abstract: E-learning is pervasive in higher education, serving as a handy training option in today's hectic culture. Despite being a widespread phenomenon in both study and practice, e-learning is still far from being utilized successfully in any setting. This is due to a lack of study of the learners' point of view as well as insufficient thinking on the ramifications for the teachers. The first part of this research is a survey of university students' opinions and experiences with e-learning. The findings are both une… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 16 publications
(20 reference statements)
0
3
0
Order By: Relevance
“…For example, with the help of specific software (Hsueh, 2018 ; Hananto, 2021 ) or algorithms (Astuti and Handoko, 2018 ; Imron and Kusumah, 2018 ), educators could identify and target the students who hold high materialism through, as well as predicting the likelihood of them starting a business in the future through machine learning (Jen and Lin, 2021 ; Prayitno et al, 2021 ; Saputro and Nanang, 2021 ; Sugiyanto, 2021 ). And then, entrepreneurial education programs could provide them with decision support systems (Azis et al, 2020 ; Fujishima, 2022 ), e-learning classes (Widiyanto et al, 2021 ), and customized training plans (Thelen, 2021 ) to improve their achievement motivation and enhance attitudes and skills regarding entrepreneurship.…”
Section: Discussionmentioning
confidence: 99%
“…For example, with the help of specific software (Hsueh, 2018 ; Hananto, 2021 ) or algorithms (Astuti and Handoko, 2018 ; Imron and Kusumah, 2018 ), educators could identify and target the students who hold high materialism through, as well as predicting the likelihood of them starting a business in the future through machine learning (Jen and Lin, 2021 ; Prayitno et al, 2021 ; Saputro and Nanang, 2021 ; Sugiyanto, 2021 ). And then, entrepreneurial education programs could provide them with decision support systems (Azis et al, 2020 ; Fujishima, 2022 ), e-learning classes (Widiyanto et al, 2021 ), and customized training plans (Thelen, 2021 ) to improve their achievement motivation and enhance attitudes and skills regarding entrepreneurship.…”
Section: Discussionmentioning
confidence: 99%
“…The results showed that both theoretical modules and workshops were effective in enhancing students' understanding of the Tripitaka teaching. The satisfaction level reached an average of 3.50, indicating the effectiveness of the online lessons in enhancing teachers' teaching skills [16].…”
Section: Conceptual Frameworkmentioning
confidence: 98%
“…In addressing this issue, companies need to create engaging and interesting experiences for customers, through strategies such as loyalty programs, active communication, and personalization. In addition, problems with poor customer service can also be a contributing factor to churn [16][17] [18]. If customers face difficulties in contacting or get a slow response from the customer service team, they may be disappointed and decide to move to another company.…”
Section: Customer Churnmentioning
confidence: 99%